Optimization of Child-Friendly Classrooms in Forming Positive Character of Students (Case Study of Students of SDN 2 Tanjungsari) - Siti Honijah; Dian Mardia; Suharyanto Soro; Nana Herdiana Abdul Rahman (Civiliza Publishing, Indonesia., 2025)
The implementation of child-friendly schools has been widely applied to educational units, but it is not optimal in the daily learning process. Some of the learning is still oriented towards cognitive aspects and classroom control that are instructive, so that the opportunity to internalize character values has not run optimally. This study aims to describe and analyze the optimization of child-friendly classrooms in shaping the positive character of students in SD Negeri 2 Tanjungsari. This research uses a qualitative research paradigm with a case study approach. Data collection methods include participatory observation, semi-structured interviews with principals, teachers, and students, and documentation studies of learning tools and school policies. The selection of respondents was carried out by purposive sampling. Data analysis was carried out using an interactive model including data reduction, data presentation, and conclusion drawn, with the application of triangulation of sources and techniques to ensure the validity of the data. The results of the study show that (1) Optimization of child-friendly classrooms is carried out through student-oriented learning planning, the implementation of participatory and humanist learning, and positive discipline-based classroom management; (2) A safe, comfortable, and inclusive classroom environment encourages students' active involvement in learning; (3) These activities have an impact on the formation of positive character of students, especially discipline, responsibility, cooperation, empathy, and confidence. The conclusion of this study is: the implementation of child-friendly classes can form the positive character of elementary school students.